Neuropsychological Performance in Patients with Asymptomatic HIV-1 Infection (2018)
Human immunodeficiency virus (HIV-1) infection and acquired immunodeficiency syndrome (AIDS) lead to neurocognitive disorders; however, there is still much knowledge to be gained regarding HIV-associated neurocognitive disorders. The purpose of this study was to assess the cognitive performance, instrumental activities of daily living, depression, and anxiety in patients with asymptomatic HIV-1 infections compared with seronegative participants without neurocognitive impairment. We studied a sample consisted of 60 patients with asymptomatic HIV-1 infections and 60 seronegative participants without neurocognitive impairment from the city of Barranquilla, Colombia, with a mean age of 36.07 years. A protocol of neuropsychological and psychopathological tests was applied to the participants. The group of patients with asymptomatic HIV infections significantly underperformed on tasks that assessed global cognitive screening, attention span, learning, phonemic verbal fluency, auditory-verbal comprehension, information processing speed, cognitive flexibility, and motor skills compared to the group of seronegative participants. No significant differences were found in memory, visual confrontation naming, vocabulary, inhibition, and instrumental activities of daily living. Additionally, the patients with asymptomatic HIV-1 infection had a higher anxiety index than the seronegative participants, but no significant difference was found in depression. A correlation was found between depression and anxiety. In conclusion, the patients with asymptomatic HIV-1 infection had lower cognitive performances than the seronegative participants in the cognitive functions mentioned above and more anxiety but still performed the instrumental activities of daily living.